1976
DOI: 10.1002/bjs.1800630709
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of clinical and operative findings associated with biliary sepsis

Abstract: A cluster analysis of 17 preoperative and 10 operative variables has been undertaken from a prospective study of 181 patients undergoing operations on the biliary tract in order to identify those with organisms in the bile who would therefore benefit from prophylactic antibiotic cover. The analysis defined populations of high risk (45 patients) and low risk (136 patients) in which the incidence of infected bile was 67 and 19 per cent respectively (P less than 0-001). Eight variables were more common in the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
6

Year Published

1982
1982
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(34 citation statements)
references
References 7 publications
0
27
0
6
Order By: Relevance
“…Retrospective study has shown that patients with bacteria in the bile are epidemiologically similar to the patients with high risk for postop infections (15 to 20%) 7 . Although, the incidence of bacteria in the bile of the patients with jaundice due to pancreatic head Ca varies from 16 to 25% without endoscopic drainage and 1-3% with drainage by plastic biliary stent 2,7,8 . With this, can understand that the inflammatory thickening of the bile duct wall due to the infection represent one of the most important factors in postop complications of patients who underwent prior endoscopic drainage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective study has shown that patients with bacteria in the bile are epidemiologically similar to the patients with high risk for postop infections (15 to 20%) 7 . Although, the incidence of bacteria in the bile of the patients with jaundice due to pancreatic head Ca varies from 16 to 25% without endoscopic drainage and 1-3% with drainage by plastic biliary stent 2,7,8 . With this, can understand that the inflammatory thickening of the bile duct wall due to the infection represent one of the most important factors in postop complications of patients who underwent prior endoscopic drainage.…”
Section: Discussionmentioning
confidence: 99%
“…There are evidences indicating relationship between bile with bacteria and the frequency of postop complications 7,8 . Retrospective study has shown that patients with bacteria in the bile are epidemiologically similar to the patients with high risk for postop infections (15 to 20%) 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these factors were studied in detail by other workers. 13,14 All patients admitted with cholangitis or who had a recent history of cholangitis gave positive bile cultures, while the bile was positive for culture in 88% of the patients admitted with jaundice alone.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the most common bacteria isolated from gallstones are aerobes (3,4), which include E. coli (5)(6)(7), Klebsiella spp. (6,7), Enterobacter fecalis (8,9), Streptococcus spp., Pseudomonas spp. (4,8,9) and Salmonella (10).…”
Section: Introductionmentioning
confidence: 99%